DYNAMICS OF ANTHROPOMETRIC INDICATORS IN THE DEVELOPMENT OF ONE-YEAR-OLD CHILDREN (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Relevance of the topic: Each infancy period of childhood is characterized by biological characteristics and helps to achieve adequate morphofunctional development at the next stage, if the natural nutrition of children is not artificially reduced. In the first year of children's life, that is, in the neonatal and breastfeeding age, the necessary conditions for adaptation to the microsocial environment, neuropsychological, and somatic conditions are formed. In general, in the first year of life, children are characterized by a faster rate of physical development, interdependence of neuropsychic and physical development, resistance to weather and environmental conditions, defects in care and nutrition than in older children.